2015
DOI: 10.1111/jsap.12274
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pancreatitis in dogs and cats

Abstract: Pancreatitis is the most common disorder of the exocrine pancreas in both dogs and cats. Ante-mortem diagnosis of canine and feline pancreatitis can be challenging. The clinical picture of dogs and cats with pancreatitis varies greatly (from very mild to severe or even fatal) and is characterised by non-specific findings. Complete blood count, serum biochemistry profile and urinalysis should always be performed in dogs and cats suspected of having pancreatitis, although findings are not-specific for pancreatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
216
1
37

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(259 citation statements)
references
References 91 publications
5
216
1
37
Order By: Relevance
“…Hematological and serum biochemical findings in cats enrolled in our study were as expected for the diseases identified . Depending on the severity of the inflammatory lesions, IBD was associated with decreases in PCV, peripheral lymphocyte counts, and serum albumin concentration.…”
Section: Discussionsupporting
confidence: 72%
“…Hematological and serum biochemical findings in cats enrolled in our study were as expected for the diseases identified . Depending on the severity of the inflammatory lesions, IBD was associated with decreases in PCV, peripheral lymphocyte counts, and serum albumin concentration.…”
Section: Discussionsupporting
confidence: 72%
“…Ultrasonography of the canine pancreas is an important noninvasive tool in the diagnosis of pancreatitis as well as evaluation of peripancreatic structures. Ultrasonographic appearance of pancreatitis include enlarged, irregularly marginated, and hypoechoic pancreas with peripancreatic hyperechoic mesenteric fat with or without focal peritoneal effusion . However, there is lack of description or observation on gastric wall thickening secondary to pancreatitis in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…However, other indicators of inflammatory response did not significantly change over time. High plasma lipase and amylase levels are known to accompany systemic inflammatory responses to tissue damage caused by, for example, gastro‐enteritis, liver disease, renal failure, acute pancreatitis, or septic peritonitis . A decrease in alkaline phosphatase across time may have been masked by a relatively short drainage period in the current study, based on a plasma half‐life approximating 72 hours in dogs .…”
Section: Discussionmentioning
confidence: 91%